Your Perfect Companion Application for Managing Your Calorie Intake - Uthai, Prasong; Eakpamitsin, Wattana; Thongsuk, Sittisak; Nakaram, Nantawan; Sukkri, Mesawadi (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to develop an Android application to calculate and track daily calorie intake and expenditure. The main programming languages used were JavaScript, SQL, Kotlin, and Dart, along with design and testing tools such as Android Studio and Figma. The goal is to enable users to conveniently manage their health and nutrition, receive appropriate nutritional and exercise recommendations, promote healthy behaviors, and reduce the risk of diseases related to unbalanced nutrition. The population of this study consisted of individuals residing in Bangkok, Thailand, and a sample of 400 participants was selected using simple random sampling. The results show that the application fully meets its objectives, excelling in ease of use, calculation accuracy, and convenient access via mobile devices. However, some limitations remain, such as an incomplete food database and lack of specific recommendations. Future development plans include integration with smart wearable devices and personalized meal recommendations.